Effect of inactivated whole-virion concentrated purified vaccine for the prevention of COVID-19 on clinical and biochemical blood parameters of immature rats - Aleksandra A. Siniugina; Natalya A. Lycheva; Anastasia A. Saprykina; Kirill L. Kryshen’; Vasiliy D. Apolokhov; Anastasiya D. Chernavtseva; Anastasiya A. Kovpak; Yuriy Yu. Ivin; Anastasia N. Piniaeva; Marina N. Makarova; Valery G. Makarov; Aidar A. Ishmukhametov (Вопросы вирусологии)
Introduction. The prevalence of new coronavirus infection (COVID-19) in 2021-2022 in the pediatric population was 9.5%, and fatal outcomes began to be recorded. In 2022–2023, the proportion of children infected with COVID-19 increased to 18%. Developing a vaccine for the pediatric population is an urgent task.